Research on the Method of Safety Warning for Shipboard Aircraft Landing. Issue 2 (January 2021) - Fang, X T; Zhang, K P; Chang, Z Z; Peng, D
Abstract: In order to ensure the landing safety of the shipboard aircraft, it is necessary to monitor the landing process of the shipboard aircraft, and give an alarm in time for the situation that may endanger the flight safety. This paper mainly studies the use of human (Landing Signal Officer and Flight Crew) and Aircraft Environment Surveillance System (AESS) and compares the defects of these two methods. On this basis, a method of shipboard aircraft landing based on the probability of landing risk is proposed. By comparing the estimated value of landing guidance error with the warning threshold of landing guidance error in the vertical and lateral direction respectively, the warning is determined according to the comparison results.